Epistemological Framework for Enhancing Higher-Order Cognition via Metaphorical Thinking Profiles - Luvia Ranggi Nastiti; Hadma Yuliani; Yokhebed Yokhebed (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the potential synergy between metaphorical thinking profiles and Higher-Order Thinking skills (HOTs) optimization in contemporary education. The research employs a qualitative methodology, utilizing literature review and content analysis to construct a comprehensive epistemological framework. The study's primary objective is to elucidate the relationship between symbolic thinking processes and the development of HOTs, specifically focusing on the dimensions of analysis, evaluation, and creation. The resultant conceptual framework demonstrates a strong correspondence between the stages of metaphorical thinking (including target concept identification, source domain exploration, structural mapping, elaboration, extension, evaluation, adjustment, and integration) and the core components of HOTs. These findings suggest that integrating symbolic thinking processes into educational strategies could significantly enhance HOTs development, potentially revolutionizing pedagogical approaches for the 21st century. This research contributes to the growing body of literature on cognitive skill development and offers practical implications for educators seeking innovative methods to prepare learners for the complexities of the global era.